Pathways towards Sustainable Performance and the Role of Green Human Resource Management Bundle Practices - Hina Ahmed,; Nadia Nasir,; Sobia Nasir, (IBT- JOURNAL OF BUSINESS STUDIES, 2022)
The purpose of this study is to investigate how Environmental Consciousness mediates the linkage between the Green Human Resource Management Bundle Practices and Sustainable Performance in the HEIs of Pakistan and this mediating relationship is totally overlooked in the formerly studies. Respectively, the study also aims to measures the association of Environmental Consciousness and Green Intellectual Capital with sustainable performance. Data for this study were gathered from HR Managers who were directly involved in the implementation of green HRM practices, as well as Chief Managers and General Managers who were directly involved in the implementation of Sustainable Performance in the education sector of Pakistan. This study's findings confirm that Green Human Resource Management practices bundle significantly improves sustainable performance. Likewise, this study finding confirms that environmental consciousness and green intellectual capital serves as a bridge between green HRM practices and sustainable performance. This study provides valuable practical implications for top management and HR Managers in the Education sector who are involved in policy making and ensuring environmental consciousness toward the implementation of Green Human Resource Management practices bundle to achieve sustainable performance.